Functional diversity of plant communities and species diversity in response to soil factors at different successional stages in karst landscapes - Wang, Yang; Huang, Hong; Ji, Yangyang; Zhou, Ruiyu; Liang, Yi; Chen, Zhifeng; Lv, Yao; Tao, Juan; Li, Li (Frontiers in Plant Science, 2025)
Karst plant communities are significantly influenced by habitat heterogeneity. Investigating the effects of species diversity and functional diversity on soil properties is essential for the restoration and conservation of forest ecosystems. Using plant communities at various successional stages in the Doupeng Mountain area of Guizhou Karst, we applied one-way ANOVA, network correlation analysis, redundancy analysis, and structural equation modeling to assess the impact of soil factors on species and functional diversity, as well as the relationships between these diversity metrics, based on data from community surveys. The results showed that (1) The Simpson, Shannon, Pielou, and Margalef species diversity indices were significantly higher in the tree stage than in the grass and shrub stages. (2) Functional richness and the Rao coefficient differed significantly across successional stages of plant communities and were highest in the tree stage, whereas functional divergence varied significantly among stages and was highest in the grass stage. (3) As succession progressed, the correlations between species diversity, functional diversity, and soil factors gradually strengthened. Five soil factors—soil nitrogen-to-phosphorus ratio, soil carbon-to-nitrogen ratio, soil bulk density, soil phosphorus content, and soil organic matter—had significant effects on the species diversity index (P < 0.05). Similarly, these five soil factors significantly influenced the functional diversity index (P < 0.05). Additionally, soil phosphorus content, soil carbon-to-nitrogen ratio, soil nitrogen-to-phosphorus ratio, and soil carbon-to-phosphorus ratio were significant factors affecting both community species diversity and functional diversity. This study demonstrated that species diversity and functional diversity of communities at different successional stages in karst landscapes differed significantly and were influenced by soil nutrient content and nutrient allocation.